PROFILE OF STRENGTH LEVEL, MUSCLE ENDURANCE, AND FLEXIBILITY OF TERA GYMNASTICS MEMBERS IN SPECIAL REGION OF YOGYAKARTA - Arjuna, Fatkurahman; Sumaryanto; Krisnanda Dwi Apriyanto; Rina Mahira (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2025)
As people age, muscle fibers tend to shrink and muscle mass decreases. This reduction in muscle mass directly affects muscle strength, endurance, and flexibility, which in turn impacts overall physical fitness in the elderly. The purpose of this study was to determine the profile of muscle strength, endurance, and flexibility among members of the TERA exercise group in the DIY. This research employed a descriptive method using a survey approach. The method used in this study is a survey method with data collection techniques through tests and measurements. The instruments used include Strength (Arm Curl Test), Endurance (2-Minute Step Test), and Flexibility (Chair Sit and Reach Test). The subjects in this study were 27 female members of the TERA gymnastics group in the DIY, selected using purposive sampling. The data analysis technique employed was frequency analysis presented in percentage form. The data analysis, presented in percentages, showed that muscle strength for the majority of participants fell into the above average category, with 26 individuals (96%), while 1 individual (4%) was in the normal category. For muscle endurance, 21 participants (72%) were in the above average category, and 6 (22%) were in the normal category. Regarding flexibility, 23 participants (86%) were categorized as above average, 2 (7%) as normal, and 2 (7%) as below average. The conclusion of this study found that the variables of muscle strength, endurance, and flexibility fall into the above-average category, which can be interpreted as good. Keywords: Muscle Endurance, Muscle Flexibility, Muscle Strength, Elderly